Reducing Discipline and Safety Issues: A District-Wide Bus-PBIS Initiative. (August 2018) - Goldin, Jamie T.; McDaniel, Sara C.
Positive behavioral interventions and supports (PBIS) is a means to proactively address student behavior in all school settings. Misbehavior on the school bus can lead to issues with safety, carry over to school and home, and hinder at-risk students' academic success. Students' behavior can be supported on the bus through the implementation of a bus-PBIS framework. School districts can implement PBIS on the bus through establishing leadership, creating a bus-PBIS framework, training, implementation, and monitoring/regeneration.